2012
DOI: 10.1111/j.1939-1676.2011.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Soybean Meal Intoxication in Cattle

Abstract: Background: Cattle are commonly fed soybean meal (SBM) and accidental intoxication sometimes occurs. Objectives: To describe the biologic and clinical features of SBM intoxication. Animals: Four steers with ruminal cannula. Methods: Controlled experimental trial. SBM was administered once at 1 and 2% of body weight (BW) via cannula at 2-month intervals.Results: This study showed a 2-phase pathogenic course for 2% BW SBM intoxication. The 1st phase (until 10 hours post-administration) is restricted to ruminal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Alkaline indigestion, an important digestive disorder of ruminants affecting the health and milk yield of dairy animals. Numerous etiological agents like soybean meal, urea, excess feeding of paddy straw, decomposed and putrefied feed as well as drinking of contaminated and sewage water have been implicated as causative factors for alkaline indigestion in bovines (Bartley et al, 1976;Raboisson et al, 2012;Haque and Dey, 1989;Misra and Tripathy, 1963;Hoflund 1967;Nagrajan and Rajmani, 1973). Administration of 5 gm urea per kg body weight along with cooked mixture of different grains via rumen fistula revealed positive correlation of rumen pH and blood ammonia concentration while rumen ammonia and blood urea were not correlated with toxicity signifying the role of readily fermentable feed in suppressing the toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alkaline indigestion, an important digestive disorder of ruminants affecting the health and milk yield of dairy animals. Numerous etiological agents like soybean meal, urea, excess feeding of paddy straw, decomposed and putrefied feed as well as drinking of contaminated and sewage water have been implicated as causative factors for alkaline indigestion in bovines (Bartley et al, 1976;Raboisson et al, 2012;Haque and Dey, 1989;Misra and Tripathy, 1963;Hoflund 1967;Nagrajan and Rajmani, 1973). Administration of 5 gm urea per kg body weight along with cooked mixture of different grains via rumen fistula revealed positive correlation of rumen pH and blood ammonia concentration while rumen ammonia and blood urea were not correlated with toxicity signifying the role of readily fermentable feed in suppressing the toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…by administration of soybean meal (SBM) via cannula at 1 and 2% of body weight revealed marked accumulation of ammonia in blood and severe metabolic alkalosis (Raboisson et al, 2012). Further authors also revealed increased ammonia concentration in blood was due to continued ammonia production from protein degradation, decreased carbohydrate fermentation and overwhelming of hepatic detoxifying capacity.…”
Section: Experimental Intoxication In Cattlementioning
confidence: 99%
See 2 more Smart Citations
“…In experiment 1, blood acid-base balance was associated with purity (Table 3). Higher blood pH has been reported to be linked to high plasma ammonia concentrations (Raboisson et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%